2021
DOI: 10.3389/fimmu.2021.749369
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analyses Identify APOBEC3A as a Genomic Instability-Associated Immune Prognostic Biomarker in Ovarian Cancer

Abstract: Ovarian cancer (OC) is one of the most malignant tumors whose mortality rate ranks first in gynecological tumors. Although immunotherapy sheds new light on clinical treatments, the low response still restricts its clinical use because of the unique characteristics of OC such as immunosuppressive microenvironment and unstable genomes. Further exploration on determining an efficient biomarker to predict the immunotherapy response of OC patients is of vital importance. In this study, integrative analyses were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
2
5
0
Order By: Relevance
“…It has also been reported that the genetically unstable type of breast cancer has a higher risk of significantly shorter recurrence-free survival and metastasis-free survival than other types ( Duijf et al, 2019 ). Consistent with previous reports, genomic instability is also associated with a poor prognosis in colorectal cancer, ovarian cancer and other tumors ( Xu et al, 2021 ; Lakbir et al, 2022 ). However, studies have shown that extreme genetic instability is correlated with a better prognosis ( Andor et al, 2017 ).…”
Section: Introductionsupporting
confidence: 92%
“…It has also been reported that the genetically unstable type of breast cancer has a higher risk of significantly shorter recurrence-free survival and metastasis-free survival than other types ( Duijf et al, 2019 ). Consistent with previous reports, genomic instability is also associated with a poor prognosis in colorectal cancer, ovarian cancer and other tumors ( Xu et al, 2021 ; Lakbir et al, 2022 ). However, studies have shown that extreme genetic instability is correlated with a better prognosis ( Andor et al, 2017 ).…”
Section: Introductionsupporting
confidence: 92%
“…APOA4 is not only a lipid-binding protein, but also has a role in the immune response [ 39 , 40 ]. Our model not only reflects the key role of CA125 for diagnosing ovarian cancer, but also suggests that the occurrence and development of ovarian cancer may be accompanied by the remodeling of cellular lipid metabolism and the complex interaction between the tumor and their hosts’ immune system [ 41 , 42 , 43 , 44 ]. These findings suggest that these proteins within sEVs found in our study can serve as diagnostic markers for ovarian cancer and provide new perspectives for therapeutic research on ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The Spearman correlation analysis of data from the TISIDB web showed that the common ICPs ( 40 ), including PDL1 (CD274), CTLA4, ICOS, LAG3, PDCD1, CD48, CD86, and TIGIT, were all significantly associated with elafin expression ( P < 0.05; Figures 7A–I ).…”
Section: Resultsmentioning
confidence: 99%